Service Quality and Pricing Strategies for Customer Satisfaction in Food Service Businesses - Maulana, Nanda Rizki; Utami, Annisa Retno (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The food service industry is experiencing intensifying competition, compelling businesses to continuously enhance service quality and adopt effective pricing strategies to improve customer satisfaction. This study aims to examine the influence of service quality and pricing strategy on customer satisfaction in the food service sector. A quantitative descriptive approach was employed, with data collected through structured questionnaires from 100 respondents selected using purposive sampling. The data were analyzed using SPSS version 27, including validity and reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²). The findings indicate that service quality has a positive and significant effect on customer satisfaction, particularly reflected in the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. Similarly, pricing strategy demonstrates a positive and significant influence on customer satisfaction, especially in terms of affordability, price–quality congruence, and perceived value. Furthermore, the simultaneous effect of service quality and pricing strategy on customer satisfaction is statistically significant. These results highlight that maintaining consistent service quality and implementing competitive, value-based pricing strategies are critical determinants in enhancing customer satisfaction within the food service industry. This study contributes both practically, by providing insights for food service managers in designing customer-oriented marketing strategies, and theoretically, by enriching the literature on service marketing and customer satisfaction.